Take advantage of the black swan to improve the urban environment - Leone, Antonio; Balena, Pasquale; Pelorosso, Raffaele (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The outbreak of the COVID-19 virus for all humanity is a typical example of the birth of the black swan, a metaphor that indicates the event of very low probability, therefore unpredictable and a source of crisis. Statistics and probability theory teach that any deterministic hypothesis of forecasting this type of event is a chimera. More concretely, it is necessary to pay attention to the resilience of the system, so the goal must be the robustness (and perhaps even anti-fragility) of the socio-ecosystem with respect to any crisis advent, not the pursuit of the specific black swan, which, by the way, takes different forms: from financial perfect storms to pandemics, to the unpredictable effects of climate change etc. During the nineteenth century Europe was involved in various pandemics, which, among other things, stimulated the birth of regulatory plans and “hygienist” urban planning approach. Similarly, the present bursting of COVID-19 leads to ever greater efforts in the direction of environmental quality, which is also the protection of health. The paper refers to the health risk due to the urban characteristics, investigating the process of Urban Heat Island (UHI) which is a cause of health risk and of the increase in air pollution, while, at the moment, there is debate about the link between air pollution and COVID-19 diffusion, also if the first scientific papers on this topic seem to confirm the correlation. In any case, the precautionary principle pushes to take the opportunity of the crisis for a more sustainable city in terms of air breathing and wellness. This paper shows that it is possible to distinguish areas of the city with different UHI-air pollution hazard, according to their shape and land use. These results allow to support the choices of the planners to pursue mitigation of climatic extremes and air pollution, contributing to health of citizens and saving money from the health system.